2010
DOI: 10.1002/app.32654
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of novel modified red mud nanocomposites based on poly(hydroxy ether) of bisphenol A

Abstract: This study dealt with the use of various quantities of modified red mud as a nanofiller in a poly(hydroxy ether) of bisphenol A (Phe) based matrix. Phe-based polymer nanocomposites reinforced with acidically and organically modified layered red mud were prepared by a conventional solvent-casting technique. The best dispersion occurred in the polymer nanocomposites where the interactions between the functional groups of the polymer matrix and those of the organic substitution of the red mud appeared to be the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In recent years, many studies have investigated different applications of red mud: as construction materials, as raw cement products, in the production of ceramics, as a geopolymer, , as composite materials, as a catalyst, as a coagulant, , as a Fenton reagent, for the capture of CO 2 , and as a metal, organic, and dye adsorbent. , In order for applications of this residue to be devised, the thermal and physical properties of red mud need to be understood. This investigation has characterized this particular Brazilian red mud in the hopes that applications can be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many studies have investigated different applications of red mud: as construction materials, as raw cement products, in the production of ceramics, as a geopolymer, , as composite materials, as a catalyst, as a coagulant, , as a Fenton reagent, for the capture of CO 2 , and as a metal, organic, and dye adsorbent. , In order for applications of this residue to be devised, the thermal and physical properties of red mud need to be understood. This investigation has characterized this particular Brazilian red mud in the hopes that applications can be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Fibres can be made from the leaves, branches and trunks through chemical process, mechanical needling and scraping or through a steam explosion process. It is extremely resilient and durable as a fi bre and has served as a foundation structure (Khanam et al ., 2011 ;Bhat et al ., 2011 ). In studies comparing it to cotton and polyester, it was found to have a high breaking tenacity, better moisture wicking properties and better moisture absorption.…”
Section: Introductionmentioning
confidence: 94%
“…Similarly, BR nanofiller of 53 µm size was used in poly (hydroxyl ether) of a bisphenol A (Phe)based nanocomposite. A matrix phase in an acidically and organically modified layered BR (as reinforcement) was further prepared by a solvent casting technique (Bhat et al, 2011). The dispersion was found to be good where the interactions between a functional group of polymer and organic substitution of BR appeared to be higher.…”
Section: Utilisation Of Br In Composite Materialsmentioning
confidence: 99%